Absence of renal cortical anisotropic backscattering artifact in feline chronic kidney disease. Issue 1 (1st January 2021) - Chou, Ping-Hsien; Heng, Hock Gan; Lin, Fang-Ju; Chen, Kuan-Sheng
Abstract: Renal cortical anisotropy backscattering artifact (CABA) is a focal hyperechoic region where the tubules are parallel to the incident ultrasound beam, reflecting most of the beams to the transducer. To investigate the association between chronic kidney disease (CKD) and the absence of renal CABA in cats. Ultrasonographic renal images of 40 cats with CKD (stage II-IV) and 36 clinically healthy cats were blindly evaluated by two observers to determine the visibility of renal CABA. Inter- and intraobserver agreements were evaluated using McNemar's test. The association between the absence of renal CABA and CKD was assessed using Fisher's exact test. Excellent intraobserver and substantial interobserver agreements were demonstrated. A significant association ( P < .0001) between absent renal CABA and CKD stage was revealed in all cats. Cats with CKD had an increased risk of the absence of renal CABA (Odds ratio, 56.0; 95% CI, 13.8–227.0) compared with the clinically healthy cats. The absence of renal CABA revealed 87.5% sensitivity and 88.9% specificity to detect CKD in all cats, and 91.7% sensitivity and 83.3% specificity in aged cats. Our study demonstrated a correlation between feline CKD and the absence of renal CABA, providing a feasible and alternative method for feline CKD evaluation.